Feasibility and inter-rater reliability of the ICU Mobility Scale - Hodgson, C.; Needham, D.; Haines, K.; Bailey, M.; Ward, A.; Harrold, Megan; Young, P.; Zanni, J.; Buhr, H.; Higgins, A.; Presneill, J.; Berney, S. (Elsevier, 2014)
Objectives: The objectives of this study were to develop a scale for measuring the highest level of mobility in adult ICU patients and to assess its feasibility and inter-rater reliability. Background: Growing evidence supports the feasibility, safety and efficacy of early mobilization in the intensive care unit (ICU). However, there are no adequately validated tools to quickly, easily, and reliably describe the mobility milestones of adult patients in ICU. Identifying or developing such a tool is apriority for evaluating mobility and rehabilitation activities for research and clinical care purposes. Methods: This study was performed at two ICUs in Australia. Thirty ICU nursing, and physiotherapy staff assessed the feasibility of the ‘ICU Mobility Scale’ (IMS) using a 10-item questionnaire. The inter-rater reliability of the IMS was assessed by 2 junior physical therapists, 2 senior physical therapists, and 16nursing staff in 100 consecutive medical, surgical or trauma ICU patients. Results: An 11 point IMS scale was developed based on multidisciplinary input. Participating clinicians reported that the scale was clear, with 95% of respondents reporting that it took <1 min to complete. The junior and senior physical therapists showed the highest inter-rater reliability with a weighted Kappa (95% confidence interval) of 0.83 (0.76-0.90), while the senior physical therapists and nurses and the junior physical therapists and nurses had a weighted Kappa of 0.72 (0.61-0.83) and 0.69 (0.56-0.81) respectively. Conclusion: The IMS is a feasible tool with strong inter-rater reliability for measuring the maximum level of mobility of adult patients in the ICU.